Microsoft Business Solutions-Axapta as a basis for automated monitoring of high technology products competitiveness; IOP Conference Series: Materials Science and Engineering; Vol. 91: VI International Scientific Practical Conference on Innovative Technologies and Economics in Engineering, Yurga, Russia, 21-23 May 2015 - Tashchiyan G. O. Grigory Olegovich (Automation and informatization, economy and management of a company, 2015)
Title screen